Cutting edge: anti-CD154 therapeutic antibodies induce infectious transplantation tolerance. - Graca, L; Honey, K; Adams, E; Cobbold, S; Waldmann, H (2000)
Nondepleting anti-CD154 (CD40 ligand) mAbs have proven effective in inducing transplantation tolerance in rodents and primates. In the induction phase, anti-CD154 Ab therapy is known to enhance apoptosis of Ag reactive T cells. However, this may not be the sole explanation for tolerance, as we show in this study that tolerance is maintained through a dominant regulatory mechanism which, like tolerance induced with CD4 Abs, manifests as infectious tolerance. Therefore, tolerance induced with anti-CD154 Abs involves not only the deletion of potentially aggressive T cells, but also a contagious spread of tolerance to new cohorts of graft-reactive T cells as they arise.